Tempeh’s contribution to the methylation cycle - Serôdio, Ana (2021)
Tempeh is a plant -based fermented food consumed as an alternative source of protein and vitamin B12 and Vitamin B9. The objective of this study is to compare the contents of vitamin B12 and amino acid profile of several cooked tempeh understand which way tempeh contributes to a healthy diet, regarding its protein composition. amino acid profile was determined by UPLC/PDA (Ultra performance liquid chromatography with photodiode array detector) and the protein quality by the calculation of protein scores (specially, methionine). Beyond that, different folate vitamers (Folic acid (FA), 5- methyltetrahydrofolate (5-MTHF), tetrahydrofolate (THF), 5-10- formyltetrahydrofolate, 5- formyltetrahydrofolate (5-CHOTHF) e 10- formyltetrahydrofolate (10-CHOTHF)) and different B12 vitamers (Hydroxycobalamin, Methylcobalamin and Cyanocobalamin) were determined by UPLC-MS/MS (Ultra performance liquid chromatography coupled to a triple quadrupole mass spectrometer with electrospray ionization (ESI)). tempeh was analyzed, one “raw” and two cooked (sautéed and stewed, after been marinated) obtained by samples from different brands and production sets, purchased in commercial surfaces. The results were carried out under a quality framework aligned with the requirements of Food Composition Databanks The sautéed sample is the one the most contribute for the population requirements, with 34,7% and 27,3% of total amino acids (for a woman with 55kg and a man with 70kg of weight, respectively), 7% of folates and 32% of B12 vitamin (particularly, hydroxycobalamin), following the “raw” sample and, finally, the marinated sample. In this way, the culinary method chosen for cooking the tempeh reveals to be an essential aspect in order to obtain higher nutritional value from it. The protein score reveals the existence of limiting amino acids in all tempeh samples, with methionine being one of them, whose contribution to daily needs, in the sautéed sample, is 26.4% for women and 20.7% for men, whose weight is 55kg and 70kg, respectively. This study reveals that tempeh is a good source of Vitamin B12 should be consumed in combination with a methionine-rich cereal, such as buckwheat avoiding confine the methylation cycle.